2013
DOI: 10.1292/jvms.12-0378
|View full text |Cite
|
Sign up to set email alerts
|

<i>Escherichia coli</i> Isolates from Calf Diarrhea in Korea and Their Virulent Genetic Characteristics

Abstract: ABSTRACT. Escherichia coli strains were isolated from the feces of 130 diarrheic calves at different farms locations in Korea. The presence of the virulence genes, such as fanC, f41, f17a, eaeA, clpG, afa-8D, sta, stx1 and stx2, in each E. coli isolate was examined. Among the 314 isolates, 157 carried one or more of the virulence genes tested in this study. The most prevalent virulence gene was clpG (45.9%), although f17A (36.9%) and afa-8D (21.7%) were also frequently observed. The sta, stx1 and eaeA genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…PCR detection of 16 E. coli isolates showed that the detection rate of eaeA genes was 12.50% ( Fig. 1, Table 3) which is correlated with Hur et al, 2013 in Korea who reported 13-17% (from diarrheic calves) of the same gene. From other studies the reported range of eaeA gene was 1.2% to 9.8% (Yuluo et al, 2010;Nguen et al, 2010;Salehi et al, 2011).…”
Section: Detection Of Pcr Productssupporting
confidence: 61%
“…PCR detection of 16 E. coli isolates showed that the detection rate of eaeA genes was 12.50% ( Fig. 1, Table 3) which is correlated with Hur et al, 2013 in Korea who reported 13-17% (from diarrheic calves) of the same gene. From other studies the reported range of eaeA gene was 1.2% to 9.8% (Yuluo et al, 2010;Nguen et al, 2010;Salehi et al, 2011).…”
Section: Detection Of Pcr Productssupporting
confidence: 61%
“…The EPEC pathotype represented 8% of E . coli isolates, slightly lower than 12% [ 75 ] and 13% [ 76 ] detection rates in Bangladesh and Korea, respectively. A decreased frequency of EPEC strain was also reported by [ 77 79 ] in Turkey, Vietnam, and Iran respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Escherichia coli has been reported as among the most common pathogens associated with diarrhea in calves, leading to high morbidity and mortality worldwide. However, remarkably few studies have been performed to evaluate the relationship between E. coli and calf diarrhea in the ROK [ 18 20 ]. In the present study, we examined the prevalence of E. coli according to age and explored the possibility of associations between E. coli and diarrhea in pre-weaned calves.…”
Section: Discussionmentioning
confidence: 99%